-2w+1=-23

Simple and best practice solution for -2w+1=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2w+1=-23 equation:


w in (-oo:+oo)

1-2*w = -23 // + 23

1-2*w+23 = 0

24-2*w = 0 // - 24

-2*w = -24 // : -2

w = -24/(-2)

w = 12

w = 12

See similar equations:

| 10+2m=14 | | 3m+5=-31 | | 9+4w=29 | | (3/4)y=51 | | 5d+12=8d-3 | | 3n+8=41 | | 7t+2=44 | | 10+5m=70 | | 4t+7=27 | | -4b+3=-33 | | 9+5w=69 | | 10n-9=9+4n | | 4w+10=-34 | | -2-4w=26 | | -10-4a=-10 | | 7n-7=28 | | 5k+3=33 | | 6+6x=-66 | | -5m+1=11 | | 4n+8=44 | | 10+7b=59 | | -5w+1=-29 | | 2x+15=6x+7 | | 2x^2=x^2/3+15 | | 7x-12=2+7x | | 3a-8=-8 | | 7+3w=22 | | -4a-7=-43 | | 8-6w=26 | | -1+4d=11 | | 7n+1=-13 | | -3x-2=31 |

Equations solver categories